Manajemen Pengembangan Kompetensi Dalam Mencapai Pencapaian Kinerja Yang Sukses: (Studi Laporan Kinerja Instansi Pemerintah BPSDM Provinsi Lampung Tahun 2019) - Adhitya Putra Pratama, Muhammad Aviv (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2021)
Apparatus competency development management is a planning process to educate, train, and manage personnel or employees to achieve the best results. Development is an apparatus investment that is future-oriented and emphasizes increasing the ability to perform new tasks in the future. The success of management can be seen by the optimal role of management elements such as man, money, method, material and machine (6M). There are two approaches to developing apparatus competence, namely the off-the-job and on-the-job training methods. In 2019 the number of apparatus with education and training certificates was 2,048 out of 16,381 apparatus, so that the main performance indicators / strategic targets were achieved by 12.50%. This value is less than the target set, which is 12.54% or it has only been achieved 99.68%.